Biološki učinki derivatov cimetne kisline - Sova, Matej (Farmacevtski vestnik, 2012)
Cinnamic acid and its derivatives are naturally occurring substances found in fruits, vegetables, spices, tea and wine. They exhibit a broad spectrum of biological activities, most notably antioxidant, anti-inflammatory, antimicrobial, antitumor, antidiabetic and hepatoprotective activity. This article presents the main cinnamic acid derivatives, their biological effects and potential applicability in the prevention and treatment of various diseases.
Keywords: antioksidanti; antioxidant; biološki učinki; cimetna kislina; protimikrobno delovanje; protitumorno delovanje